THEME-POLYSEMY RELATIONS IN ONLINE NEWS HEADLINES: A PRAGMATIC ANALYSIS - Tri Utami; Naza Fanisa; Deliana Deliana (Universitas HKBP Nommensen, 2026)
Headlines represent one of the most condensed forms of media discourse, requiring journalists to communicate complex events with minimal linguistic resources. To achieve brevity and impact, headlines frequently employ polysemous verbs whose meanings must be inferred rapidly and accurately despite limited context. This study investigates how thematic organization, within the framework of Systemic Functional Linguistics (SFL), functions as a pragmatic mechanism that constrains the interpretation of polysemous expressions in English online news headlines. Using a qualitative descriptive design, thirty headlines from BBC News, The Guardian, and CNN International (January-February 2025) were analyzed through theme–rheme structure, lexical semantics, and Relevance Theory. The findings reveal a highly consistent pattern: 26 of the 30 headlines (86.7%) positioned polysemous verbs in the rheme, while the theme activated domain-specific frames economic, political, environmental, or technological that guided readers toward the intended meaning. These results demonstrate that thematic framing systematically reduces ambiguity and supports relevance driven interpretation in contexts with minimal co text. This study contributes to SFL by providing empirical evidence that the theme is not only a textual point of departure but also a meaning constraining device that shapes semantic interpretation, and it extends Relevance Theory by showing how thematic cues narrow inferential space and lower processing effort. Practically, the findings offer implications for media literacy and journalism, as recognizing how themes guide interpretation can help readers identify framing strategies in digital news and support journalists in managing potential ambiguity while maintaining communicative economy.